Measurement of Gastric Emptying Using a 13C-octanoic Acid Breath Test with Wagner-Nelson Analysis and Scintigraphy in Type 2 Diabetes - Trahair, Laurence G; Nauck, Michael A; Wu, Tongzhi; Stevens, Julie E; Buttfield, Madeline D; Hatzinikolas, Seva; Pham, Hung; Meier, Juris J; Rayner, Christopher K; Horowitz, Michael; Jones, Karen L (Experimental and Clinical Endocrinology & Diabetes, 2022)
Introduction Breath tests utilising 13C-labelled substrates for the assessment of gastric emptying have been applied widely. Wagner-Nelson analysis is a pharmacokinetic model that can be utilised to generate a gastric emptying curve from the % 13CO2 measured in breath samples. We compared Wagner-Nelson analysis with (i) scintigraphy and (ii) conventional breath test modelling to quantify gastric emptying in type 2 diabetes.Methods Thirteen patients (age 68.1±1.5 years, body mass index 31.0±0.9 kg/m2, HbA1c 6.3±0.2%) consumed a mashed potato meal comprising 65 g powdered potato, 20 g glucose, 250 ml water, an egg yolk labelled with 100 μL 13C-octanoic acid and 20MBq 99mTc-calcium phytate. Scintigraphic data were acquired and breath samples collected for 4 hours after the meal. Gastric emptying curves were derived based on each technique; the 50% emptying time and intragastric retention at 60 min were also calculated.Results With Wagner-Nelson analysis, a Kel=0.60 (the elimination constant) best approximated the scintigraphic gastric emptying curve. There was a relationship between the T50 calculated with scintigraphy and by both Wagner-Nelson Kel=0.60 (r2=0.45, P<0.05) and conventional analysis (r2=0.44, P<0.05). There was no significant difference in the 50% gastric emptying time for scintigraphy (68.5±4.8 min) and Wagner-Nelson Kel=0.60 (71.3±4.5 min), however, the 50% gastric emptying time calculated by conventional analysis was much greater at 164.7±6.0 min (P<0.001).Conclusion In type 2 diabetes, gastric emptying of a mashed potato meal measured using a 13C-octanoic acid breath test analysed with Wagner-Nelson Kel=0.60 closely reflects measurements obtained with scintigraphy, whereas, in absolute terms, the conventional breath test analysis does not.
Keywords: gastric emptying; breath test; scintigraphy; Wagner-Nelson; glucose